Рестрикционное картирование хлоропластной ДНК пяти видов Nicotiana - Комарницкий, И.К.; Самойлов, А.М.; Глеба, Ю.Ю. (Биополимеры и клетка, 1989)
Проведено рестрикционное картирование пяти видов Nicotinia, три из которых австралийского происхождения — N. еаstii, N. occidentalis, N. exigua и два американского — N. undulata, N. chinensis. Проведено рестрикційне картування п’яти видів Nicotinia, три з яких австралійського походження – N. еаstii, N. occidentalis, N. exigua і два американського – N. undulata, N. chinensis. Restriction mappings for five Nicotiana species of australian origin — N. eastii, N. occidentalis, N. exigua and american one — N. undulata, N. chinensis have been constructed using Sal Gl, Xho I, Pst 1, Pvu II and Sma I restriction endonucleases. Most of changes found in chloroplast DNA are positioned in the central part of the large single-copy region and are adjacent to inverted repeats. These changes are, probably, due to deletions and/or insertions. On the contrary, the changes in the small single-copy region are mainly caused by point mutations.